2016
DOI: 10.1038/mtna.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

A Glu-urea-Lys Ligand-conjugated Lipid Nanoparticle/siRNA System Inhibits Androgen Receptor Expression In Vivo

Abstract: The androgen receptor plays a critical role in the progression of prostate cancer. Here, we describe targeting the prostate-specific membrane antigen using a lipid nanoparticle formulation containing small interfering RNA designed to silence expression of the messenger RNA encoding the androgen receptor. Specifically, a Glu-urea-Lys PSMA-targeting ligand was incorporated into the lipid nanoparticle system formulated with a long alkyl chain polyethylene glycol-lipid to enhance accumulation at tumor sites and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The opposite was observed for particles designed for tumor accumulation. Increasing the amount of PEG‐C18 from 2.5 to 5.0 mol% resulted in elongated circulation times and an increased accumulation in tumor tissue . This highlights how, by altering the PEG anchor and density, LNP pharmacokinetics and tissue distribution may be tuned for specific applications.…”
Section: Design Principles For Lipid Nanoparticles For Sirna Deliverymentioning
confidence: 95%
See 1 more Smart Citation
“…The opposite was observed for particles designed for tumor accumulation. Increasing the amount of PEG‐C18 from 2.5 to 5.0 mol% resulted in elongated circulation times and an increased accumulation in tumor tissue . This highlights how, by altering the PEG anchor and density, LNP pharmacokinetics and tissue distribution may be tuned for specific applications.…”
Section: Design Principles For Lipid Nanoparticles For Sirna Deliverymentioning
confidence: 95%
“…For LNPs containing PEG‐C16 and C18, maximally 35% and 25%, respectively, accumulated in the liver and these maxima were reached at a later time point compared to PEG‐C14. Not surprisingly, for extra hepatic targets such as tumors, longer circulating LNPs using PEG‐C18 are used to improve tissue accumulation …”
Section: Design Principles For Lipid Nanoparticles For Sirna Deliverymentioning
confidence: 99%
“…Although there is preclinical evidence that LNP-siRNA can induce hepatic gene silencing following subcutaneous administration, the dose needed for effective gene silencing is considerably higher than for intravenously administered formulations [147]. Of note, while LNP-siRNA systems have been optimized for hepatic gene silencing, preclinical studies have also demonstrated their ability to induce effective gene silencing in extrahepatic target sites including the bone [244] and tumors [245,246]. A major area of interest is applying LNP-siRNA for immunotherapy, by silencing target genes in lymphocytes following intravenous administration for immunotherapy [247][248][249][250][251] (covered by Peer et al in this issue [252]).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…LNP-siRNA systems containing PEG-DSG (3-5 mol%; 30 nm diameter) that exhibit long circulation lifetimes (t 1/2 of 10-12 h) have been used to knock down the androgen receptor (AR), a fundamental driver of prostate cancer, in an LNCaP xenograft model [68]. However, the dose of LNP-siRNA required to achieve appreciable gene silencing was 30 mg/kg, more than 6,000 times higher than required to achieve an ED 50 in hepatocytes.…”
Section: Design Of Lnp-sirna For Extrahepatic Targetsmentioning
confidence: 99%
“…However, the dose of LNP-siRNA required to achieve appreciable gene silencing was 30 mg/kg, more than 6,000 times higher than required to achieve an ED 50 in hepatocytes. In an effort to improve potency, a targeting ligand for the prostate-specific membrane antigen was incorporated, resulting in improved gene silencing activity [68], but not the orders of magnitude improvement required for clinical potential. Similarly, knockdown activity and tumor growth delay were reported at distal tumors in an enzalutamide-resistant LNCaP xenograft model when LNP-siRNA against clusterin was used in combination with AR-ASO [69].…”
Section: Design Of Lnp-sirna For Extrahepatic Targetsmentioning
confidence: 99%